Cartografia tátil : inclusão dentro e fora da escola - Santos, Lindeval José dos (2021)
The present work presents reflections on the teaching of Geography from an inclusive education perspective, more specifically on tactile cartography, which promotes inclusion through the development of cartographic representations accessible to blind or low vision people. Theoretical and methodological reviews about tactile cartography offer support for the development of reflections and practices in the teaching of geography that include mainly the teaching and learning of blind people. In order to dialogue with Geography teachers, workshops, conversation circles and a questionnaire were held. The workshops sought to socialize adaptation activities and the creation of teaching material for blind and visually impaired students; Even with all technological advances, during the workshops we seek to socialize low-cost artisanal techniques are efficient and affordable alternatives for teachers and students. Tactile cartography has offered efficient alternatives for the development of inclusion mechanisms inside and outside the school, helping to guarantee and promote the right and to consolidate an inclusive Geography, that is, committed to a more just and egalitarian society.